Artificial Intelligence and its Impact on Some Economic Fields - اسبر ميساء (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Artificial Intelligence has had a huge impact on all economic and social sectors, and this impact steadily increasing. Many countries and even large companies around the world have expressed their desire to develop their strategies to suit the characteristics of artificial intelligence. Many view artificial intelligence as an engine of productivity and economic growth. It can increase the efficiency of getting things done and significantly improve the decision-making process by analyzing the large amounts of data available to it. It can also lead to the creation of new products, services, markets and industries, thus enhancing consumer demand and generating new revenue sources. It also has major impacts on education, health, and many services. The current study cites some studies that shed light on the different roles of artificial intelligence, with the aim of getting to know more closely these roles in many areas of economic life. It also reviews the experiences of some Arab countries in this context.